Сто великих тайн - Непомнящий Николай Николаевич (100 великих, 2005)
На обл. авт. не указаны Экземпляры: ф.2 (ретро) / Инвентарный номер: 40100 / Цена: / Сис.шифр: 63.3 / Авт.знак: Н53 / ГРНТИ: 03.09 / ББК: 20.3 я9